2019
DOI: 10.37358/rc.19.11.7662
|View full text |Cite
|
Sign up to set email alerts
|

Could Chemical Composition of Stone Influence Percutaneous Nephrolithotomy in the Management of Staghorn Calculi?

Abstract: The management of large renal stones is a challenging situation for the urologists. PCNL (percutaneous nephrolithotomy) represents the elective procedure and can be performed as monotherapy or combined with other techniques. This is a retrospective study on 75 patients diagnosed with staghorn calculi at Prof. Dr. Th. Burghele Clinical Hospital who underwent PCNL between 01.01.2018 to 31.06.2018. The aim of this study is to evaluate the correlations between the staghorn chemical composition, the stone free rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Apart from general considerations regarding risk factors for UTIs in both genders such as reduced fluid intake, delayed voiding, lithiasis of the urinary tract or chronic constipation, more specific risk factors in the general female population have been described such as anatomic conditions (short urethra) or age-related circumstances such as pregnancy, recent sexual intercourse, use of diaphragm or spermicides in young and adult women, or hormone-induced or anatomical modifications due to menopause in older women [4,[7][8][9][10]. The factors contributing to the rising incidence in older women are their health status, presence of diabetes mellitus, history or current catheterization, residential status, history of antibiotic use, or spinal cord dysfunction [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from general considerations regarding risk factors for UTIs in both genders such as reduced fluid intake, delayed voiding, lithiasis of the urinary tract or chronic constipation, more specific risk factors in the general female population have been described such as anatomic conditions (short urethra) or age-related circumstances such as pregnancy, recent sexual intercourse, use of diaphragm or spermicides in young and adult women, or hormone-induced or anatomical modifications due to menopause in older women [4,[7][8][9][10]. The factors contributing to the rising incidence in older women are their health status, presence of diabetes mellitus, history or current catheterization, residential status, history of antibiotic use, or spinal cord dysfunction [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Real UTIs in the adult male population have an incidence of approximately 5–8 per year per 10,000, usually due to sexually transmitted infections that are related to the urethra and prostate [ 7 ]. With age, the incidence of diagnosed infections significantly increases in the elderly male population [ 8 , 9 ]. Previous studies revealed differences of occurrence in 1000 men based on age group population and reported 0.9 up to 2.4 cases before 55 years and about 7.7 cases after 85 years old [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…More complicated infections appear in older men due to prostate enlargement, which causes bladder obstruction and leads to urinary stasis and the appearance of the disease [ 7 ]. Recurrent infection with more virulent microorganisms appears in men with urinary tract abnormalities or when an ineffective treatment does not succeed to eradicate the resistant bacteria [ 9 , 14 ]. The most common causes underlying UTIs in men are represented by benign prostatic hyperplasia, urethral stricture, bladder neck obstruction, bladder stone, bladder tumor, bladder diverticula, prostate cancer, foreign bodies, tight phimosis, and detrusor-sphincter dyssynergia.…”
Section: Introductionmentioning
confidence: 99%